Mandibular metastasis in a patient with follicular carcinoma of thyroid - Chetan J Bhadage; Sagar Vaishampayan; Hemant Umarji (Wolters Kluwer Medknow Publications, 2012)
Mandibular metastasis due to thyroid carcinoma is not very frequent and the cases described in the literature are few. Due to its bloodstream dissemination, most of them are a consequence of the follicular variant of thyroid carcinomas. We are presenting a case in which the metastatic lesion of mandible was detected before diagnosis of primary malignancy.